1993
DOI: 10.1002/ccd.1810300220
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transradial artery approach for coronary stent implantation

Abstract: A new approach for implantation of Palmaz Schatz coronary stents is reported. We describe the technique and rationale of coronary stenting with miniaturized angioplasty equipment via the radial artery. This technique is illustrated in three patients. One patient underwent Palmaz Schatz stent implantation for a saphenous vene coronary bypass graft stenosis, the second patient for a restenosis in the anterior descending coronary artery after atherectomy, and the third patient for a second restenosis after balloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
167
2
10

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(182 citation statements)
references
References 12 publications
3
167
2
10
Order By: Relevance
“…1,2) Thereafter, both transradial coronary intervention (TRI) and transradial coronary angiography (TRA) have been widely employed in Japan. It has been accepted among cardiologists that the transradial procedure produces fewer vascular complications than the conven-tional transfemoral and transbrachial approaches [3][4][5][6][7] because blood supply from the palmar arch by both the radial and ulnar arteries is adequate.…”
mentioning
confidence: 99%
“…1,2) Thereafter, both transradial coronary intervention (TRI) and transradial coronary angiography (TRA) have been widely employed in Japan. It has been accepted among cardiologists that the transradial procedure produces fewer vascular complications than the conven-tional transfemoral and transbrachial approaches [3][4][5][6][7] because blood supply from the palmar arch by both the radial and ulnar arteries is adequate.…”
mentioning
confidence: 99%
“…The serum level of plasma renin activity was 2.70 ng/mL/ hour (normal range, 0.20-2.70). An ECG taken 18 years prior to admission was normal, whereas that taken on admission showed negative T waves in leads I, a VL, and V [1][2][3][4][5][6] . Two-dimensional transthoracic echocardiography revealed that the apical wall of the left ventricle was thin and dyskinetic, suggesting an apical old myocardial infarction.…”
Section: Case Reportmentioning
confidence: 99%
“…4) It has been reported that the radial artery approach provides an alternative entry site for coronary angiography, angioplasty, and stenting. 5,6) The major advantage is a significant reduction in access site-related vascular complications such as vascular repair or blood transfusion during coronary intervention. 7) A few recent reports have shown that renal artery interventions also could employ the radial approach as a vascular access site.…”
mentioning
confidence: 99%
“…In early 1990, Kiemeneij and Laarman performed balloon angioplasty and stenting through radial artery [3] and in the access study, Kiemeneij et al showed that there are no significant differences between any of the three tested approaches in terms of success of coronary angiography or angioplasty or duration of procedure [4]. But, despite wide recognition trans-radial artery PTCA has not received greater acceptance compared to femoral access.…”
Section: Introductionmentioning
confidence: 99%